Analysis of the income and productivity of the trade sector in Ecuador. A study for the years 2012, 2019, and 2022 - Sarmiento Moscoso, Luis Santiago (2025)
This research examines the effect of certain economic variables on the economic growth of the commercial sector in Ecuador during the years 2012, 2019, and 2022, by analyzing their impact on operating income in relation to the number of workers, gross capital formation, and intermediate inputs. To this end, the Cobb-Douglas production function is estimated using an econometric model initially estimated through Ordinary Least Squares (OLS) and subsequently corrected using Newey-West standard errors due to the detection of autocorrelation and heteroscedasticity in the initial results. For this study, data from the Superintendence of Companies, Securities and Insurance were used, paying special attention to characteristics such as company size and location. Among the main findings, it is observed that the number of workers and intermediate inputs are the most influential factors in the economic growth of the Ecuadorian commercial sector, highlighting the importance of human capital in increasing productivity and, therefore, efficiency. The implementation of policies aimed at reducing disparities between small and large enterprises is emphasized, along with the creation of incentives in areas such as taxation, access to investment credit, and the development of training programs for employed personnel. These measures would improve workers’ skills, increase productivity and competitiveness in the Ecuadorian commercial sector, and promote more equitable and sustainable development.